The Influence of Usage and Spatial Experiences on Personal Desirability of a Park Plan: Using Structural Equation Modeling—A Case Study of a Park near a Station in a Suburban City in Japan - Qin Huang; Ryosuke Shimoda; Yingnan Jiao; Jingyi Yin; Junhua Zhang; Shiro Takeda (Land)
Owing to lifestyle changes since COVID-19, new needs for various usages and spatial experiences of open spaces have become apparent. Suburban parks and green spaces are thought to be suitable uses. This study used structural equation modeling to examine the direct and indirect effects of diverse usages and experiences on the desirability of three proposed park plans for a major park in City A, near Tokyo, based on questionnaire survey data. The findings highlight the importance of “Nature, Passive, and Healing” usage, including nature experiences and small-group activities. “Nature, Passive, and Healing” is negatively affected by “Gathering and Active” but positively by “Multifunctional and Borderless”. A potential for significant improvement in park desirability was also found by linking “Nature, Passive, and Healing” to “Multifunctional and Borderless”. For those aged 60 and older, the indirect effect of “Multifunctional and Borderless” via “Nature, Passive, and Healing” was large and significant, whereas its direct effect was not. “Multifunctional and Borderless” park usage was also been proven to have the greatest impact on female users, whereas, for males, “Nature, Passive, and Healing” had the largest impact. These results emphasize the importance of designs that balance diverse usages and ensure appropriate distancing to meet new needs.